Moraxella nonliquefaciens–Associated Ecthyma Gangrenosum in a Pediatric Patient With Cancer. (5th April 2022) - Starkey, Grant; Lee, Erica; Clarey, Dillon; Georgesen, Corey
Abstract: In this brief report, we describe a 16-year-old patient with pre–B-cell acute lymphoblastic leukemia on chemotherapy who presented to the emergency department with a fever and "bruise-like" area on his left forearm. Empiric antibiotic therapy was initiated, and initial tissue biopsy demonstrated findings consistent with ecthyma gangrenosum. On day 4 of admission, initial blood cultures grew Moraxella nonliquefaciens, and targeted antibiotic therapy was initiated and continued for a total of 21 days. The patient was discharged after 6 days of in-patient therapy and made a full recovery. M. nonliquefaciens has been reported to be associated with multiple types of infection, but no cases of M. nonliquefaciens –associated ecthyma gangrenosum were identified in the literature review for this report. Given this unique case and the empiric risks and broad differential associated with cutaneous manifestations in immunocompromised patients, obtaining a skin biopsy for histological examination is imperative for diagnostic workup.